2021
DOI: 10.3390/ijerph182010859
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Recruiting Latinos in Decídetexto—A Smoking Cessation Clinical Trial from an Emergency Department Patient Registry

Abstract: There is an underrepresentation of Latinos in smoking cessation clinical trials. This study describes the feasibility and effectiveness of recruiting Latino smokers in the U.S. from an emergency department (ED) patient registry into a randomized smoking cessation clinical trial. Recruitment occurred from the Hackensack University Medical Center ED. Potential participants were contacted from a patient registry. The primary outcome was whether the participant responded to a call or text. Secondary outcomes inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Although patient registry calls yielded the highest number of participants, it was among the lowest efficiency ratio for eligibility and enrollment. This is in contrast to previous research that has reported the feasibility and cost-effectiveness of recruiting participants via calls from patient registries via a research associate program [ 20 , 33 ].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Although patient registry calls yielded the highest number of participants, it was among the lowest efficiency ratio for eligibility and enrollment. This is in contrast to previous research that has reported the feasibility and cost-effectiveness of recruiting participants via calls from patient registries via a research associate program [ 20 , 33 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Literature on the recruitment of Latinos into clinical trials has described the use of different recruitment strategies [ 19 - 23 ]. Some studies have recruited Latinos through proactive recruitment in which study staff directly contact individual potential participants [ 20 , 24 ] and reactive recruitment in which studies disseminate information via mass media and potential participants must contact the study themselves [ 19 , 21 , 25 ]. Often, recruitment studies emphasize including Latino researchers, fostering community connections to build trust, and using culturally and linguistically tailored recruitment materials delivered through culturally appropriate outlets such as Latino newspapers [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the strengths of this study and a possible facilitator of recruitment is that this research builds upon our established history of smoking-cessation treatment and research within the community [ 20 , 60 , 61 , 62 , 63 , 64 ]. Moreover, this work is grounded in principles of community-based participatory research (CPBR).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the recruitment of Black and Latino individuals into tobacco-control (e.g., smoking cessation) studies have described the use of different recruitment methods [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. These studies have recruited Black and Latino participants through proactive (also known as active or direct) recruitment, which includes direct interaction with potential participants [ 27 ], and reactive (also known as passive or indirect) recruitment, where individuals contact the study themselves [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Latinos also report a general lack of cultural sensitivity within existing Spanish language resources for smoking cessation [ 11 ]. Although barriers to accessing smoking cessation resources exist, when provided with access, Latinos are interested in participating in smoking cessation programs and in using smoking cessation treatments to support quit attempts [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%